Humanist but not radical: The educational philosophy of Thiruvalluvar Kural - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2021)
Humanist ideas in education have been promoted by both Western thinkers and classical wisdom texts of Asia. Exploring this connection, I examine the educational philosophy of an iconic ancient Tamil (Indian) text, the Thiruvalluvar Kural, by juxtaposing it with a contemporary humanist classic, Paulo Freire’s Pedagogy of the Oppressed. As this comparative study reveals, both texts offer humanist visions of relevance to education, politics, and society. Notably, however, the Kural takes what might be described as a more mainstream humanist stance vis-à-vis Freire’s radical humanist approach. Nevertheless, both educational philosophies share a common humanist bond representing important breakthroughs within their own given contexts. More specifically, the Kural supports a shift in consciousness and social practices away from caste rigidity, superstition, and pre-humanist beliefs while Freire championed transitioning from rigid, top-down and alienating educational delivery models and economic systems to learning processes and societies that are more democratized, dialogic and egalitarian.